2010
DOI: 10.1111/j.1440-1797.2009.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome in haemodialysis: Prevalence, link with quality of life and depression

Abstract: IBS is highly prevalent in HD patients. Presence of IBS is closely related with HRQOL and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 28 publications
(33 reference statements)
3
15
3
Order By: Relevance
“…16 A summary of the published studies reporting on GI symptoms or GI syndromes in patients with ESRD is presented in Table 4. 4,6,[14][15][16][17][18][19][20] Upper GI symptoms were particularly common compared with lower GI symptoms and our result is consistent with what has been reported in the literature (38% to 74%). 14,17,21,22 Among our patients, dyspepsia was the most common with almost 45% of the patients having experienced dyspepsia in the previous 12 months.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…16 A summary of the published studies reporting on GI symptoms or GI syndromes in patients with ESRD is presented in Table 4. 4,6,[14][15][16][17][18][19][20] Upper GI symptoms were particularly common compared with lower GI symptoms and our result is consistent with what has been reported in the literature (38% to 74%). 14,17,21,22 Among our patients, dyspepsia was the most common with almost 45% of the patients having experienced dyspepsia in the previous 12 months.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, our study is the first study to have assessed this correlation. Two other studies without control arm showed the presence of IBS to be associated with impaired psychosocial well‐being . On the other hand, although Cano et al .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations